Biological Diversity Of Farm Animals In Bangladesh: A Review - Hamid, MA (SAARC Journal of Agriculture, 2020)
The present study attempts to examine the scenario of farm animal’s genetic diversity and their distribution pattern in Bangladesh. The major components of farm animals in Bangladesh are cattle, buffalo, goat, sheep, chicken and duck which are being raised in a mixed farming system integrated with crop agriculture. The biological diversity most of farm animals is of native origin. Cattle and chicken are the two major species which are being manipulated genetically either through inclusion of exotic blood and/or import of live animals and birds. Buffalo, goat, sheep and duck are also being crossed to some extent with exotic germplasms. Other species like pigeon, quail, and guinea fowl are also available in the country. This paper has also shown the population and list of different breed/type of farm animals available in Bangladesh which helps to meet the public priorities such as, their production and reproduction, their management practices, their survivability etc. SAARC J. Agri., 17(2): 15-29 (2019)